Analisis Penghasilan, Pekerjaan, dan Usaha Masyarakat di Masa Pandemi Melalui Penerapan Data Sains - Nafi'iyah, Nur; Maghfiroh, Syafaatul (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2021)
Activities in some sectors experience a decrease in revenue due to the Covid-19 outbreak, for example, the business of traders who experience a decline turnover. From some respondents who work in the field of trade, entrepreneurship, self-employment experience the impact of the Covid-19 pandemic. This can be seen from the results of questionnaire distributed through google form https://bit.ly/2DiRYzL. Despite the pandemic, work and learning activities still have to run online, for example, conducting online Student Community Service (KKN), with socialization activities to fill out questionnaires related to the impact of the Covid-19 pandemic. In addition, the author also held online KKN activities by promoting tourist attractions in Sekaran village through https://www.youtube.com/watch?v=Ed3bdRIxlpY. The purposes of distributing questionnaire are to know the impact of the pandemic and in order to obtain solutions. This questionnaire was distributed to KKN places, namely Sekaran, Babat, Kebonsari, Turi, Kentong, Tunggul, Priyoso villages in Lamongan Regency, and Bayureno, Â Bojonegoro, and Banyulegi Mojokerto. The questionnaires that have been completed were then analyzed using basic statistics such as average value, maximum value, and minimum value. The results of the distribution of questionnaires obtained 990 respondents, with an analysis of 77% of respondents experienced changes in income during the pandemic. Jobs affected by Covid-19 are traders, entrepreneurs, self-employed, farmers and online hired motorcycle drivers. Their incomes decreased by 50% to 68%. There were 43 layoffs out of 990 respondents.